2020
DOI: 10.3892/or.2020.7703
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs target the Wnt/β‑catenin signaling pathway to regulate epithelial‑mesenchymal transition in cancer (Review)

Abstract: Epithelial-mesenchymal transition (EMT), during which cancer cells lose the epithelial phenotype and gain the mesenchymal phenotype, has been verified to result in tumor migration and invasion. Numerous studies have shown that dysregulation of the Wnt/β-catenin signaling pathway gives rise to EMT, which is characterized by nuclear translocation of β-catenin and E-cadherin suppression. Wnt/β-catenin signaling was confirmed to be affected by microRNAs (miRNAs), several of which are down-or upregulated in metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 195 publications
(199 reference statements)
0
33
0
Order By: Relevance
“…Restoration of miR-122 expression in HCC results in suppression of tumor growth and metastasis, and enhances chemosensitivity, suggesting that miR-122 functions as a tumor suppressor against HCC [ 47 ]. To date, several target genes of miR-122, such as cyclin G1, a disintegrin, and metalloprotease 10 (ADAM10), Wnt family member 1, Snail1/2, and pyruvate kinase M2, were identified to modulate hepatocarcinogenesis, the EMT, angiogenesis, and metabolism of HCC [ 47 , 48 , 49 , 50 , 51 ]. Our results indicated that G9a represents a novel, important target gene of miR-122 in regulating HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of miR-122 expression in HCC results in suppression of tumor growth and metastasis, and enhances chemosensitivity, suggesting that miR-122 functions as a tumor suppressor against HCC [ 47 ]. To date, several target genes of miR-122, such as cyclin G1, a disintegrin, and metalloprotease 10 (ADAM10), Wnt family member 1, Snail1/2, and pyruvate kinase M2, were identified to modulate hepatocarcinogenesis, the EMT, angiogenesis, and metabolism of HCC [ 47 , 48 , 49 , 50 , 51 ]. Our results indicated that G9a represents a novel, important target gene of miR-122 in regulating HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Wnt signaling/β-catenin pathway dysregulation is involved in cancer genesis, including oral cancer. This pathway is accompanied by various mechanisms, such as epithelial-mesenchymal transition and involvement of various miRNAs [ 51 , 52 ]. Participation of miR-30c-5p targets in this signaling pathway as shown by the pathway enrichment analysis underlies its role in oral cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several important pathways such as Wnt, mTOR, MAPK signaling, and miRNA in cancer were significantly enriched in KEGG pathway enrichment analysis (71)(72)(73)(74)(75). Recent reports suggest that Wnt signaling pathway regulates several crucial events, including EMT, cell migration, cell proliferation, and polarity of cells (76)(77)(78)(79)(80)(81). The association of Wnt signaling pathway and dysregulation of miRNA has been linked together in various cancer types.…”
Section: Discussionmentioning
confidence: 99%